Replication-Competent Reporter-Expressing Viruses (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Recombinant viruses expressing reporter fluorescent or bioluminescent proteins are an excellent option to evaluate the dynamics of viral infection progression in both cultured cells and/or validated animal models of viral infection. Reporter proteins are valid surrogates for direct detection of infected cells in vitro and in vivo, without the use of secondary methodologies to identify infected cells. By eliminating the need of secondary labeling, tractable replicating-competent, reporter-expressing viruses provide an ideal approach to monitor viral infections in real time, representing a significant advance in the study of the biology of viruses, to evaluate vaccination approaches, and to identify new therapeutics against viral infections using high-throughput screening settings. In this Special Issue "Replication-Competent Reporter-Expressing Viruses" we review replication-competent, reporter-expressing viruses belonging to different families, methods of characterization, and applications to facilitate the study of in vitro and in vivo viral infections. We also seek to discuss disadvantages and limitations associated with these reporter-expressing viruses. Finally, we provide rational future perspectives and additional avenues for the development, characterization, and applications of recombinant, reporter-expressing, competent viruses.